2022
DOI: 10.1186/s12877-022-03405-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative gait analysis in mild cognitive impairment, dementia, and cognitively intact individuals: a cross-sectional case–control study

Abstract: Background Cognitive age-related decline is linked to dementia development and gait has been proposed to measure the change in brain function. This study aimed to investigate if spatiotemporal gait variables could be used to differentiate between the three cognitive status groups. Methods Ninety-three older adults were screened and classified into three groups; mild cognitive impairment (MCI) (n = 32), dementia (n = 31), and a cognitively intact (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
1
16
1
Order By: Relevance
“…With some variation, there was an overall trend that groups with more severe cognitive impairment walked with shorter steps both during the TUG condition and the two TUGdt conditions. These results are in accordance with previous studies where shorter stride/step length has been found to occur in groups with dementia compared to MCI and/or controls [10,38] as well as between people with MCI and controls [39]. However, those studies were conducted while participants performed straight, overground walking, primarily in movement laboratory settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With some variation, there was an overall trend that groups with more severe cognitive impairment walked with shorter steps both during the TUG condition and the two TUGdt conditions. These results are in accordance with previous studies where shorter stride/step length has been found to occur in groups with dementia compared to MCI and/or controls [10,38] as well as between people with MCI and controls [39]. However, those studies were conducted while participants performed straight, overground walking, primarily in movement laboratory settings.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, assessments have generally been conducted in motion laboratory settings (i.e. advanced equipment) [10,12,15] or have been conducted in clinical settings requiring spacious environments [13], which may not be available in most clinical facilities and therefore hampers potential for implementation. Also, few studies have been able to discriminate between different groups with less severe impairment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This study underscores the potential of curved path walking as a valuable tool for early MCI detection, a crucial step in enhancing patient care and intervention strategies. Despite previous research highlighting dual-task walking’s importance in dementia [ 49, 50 ], some studies found no significant difference in MCI detection using dual-task straight walking [ 51, 52 ]. Our findings suggest curved path walking may be more sensitive for MCI detection, indicating that integrating cognitive tasks with curved walking could improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 97%
“… Ghoraani et al (2021) , Montero-Odasso et al (2020) , and Ramírez and Gutiérrez (2021) have all shown that slowed gait speed while dual-tasking can not only differentiate MCI from NC individuals, but can also predict its progression to dementia. A recent study showed that most of the spatiotemporal gait variables could discriminate between dementia and cognitively intact individuals under single and dual tasks ( Bovonsunthonchai et al, 2022 ). The DT in this study is counting backward which is similar to the DT calculation in our study.…”
Section: Discussionmentioning
confidence: 99%